Microfoundations of ecosystems: The theory-led firm and capability growth. (May 2023) - Felin, Teppo; Foss, Nicolai
We argue that firm-specific theories are critical for understanding the emergence and evolution of ecosystems. We first highlight how existing research on ecosystems lacks microfoundations and tends to be overly structural. We focus on the theory-led firm—the role that a firm-specific theory plays in capability development and the associated growth of ecosystems. Ecosystems are contingent on firm-specific theories of value. We also discuss the implications of our arguments for search- and demand-based approaches to ecosystems and point toward a theory-based and supply-side alternative.